Prevalence of Helicobacter pylori infection and its Associated Risk Factors among symptomatic Residents of Sulaimani city, Kurdistan region, Iraq, 2020 - Ali, Seerwan Hama Rashid; Salih, Sabiha Sharif; Hama Sour, Taib Ahmed; Raouf, Goran Mohammad; Rahim, Araz Latif (Kurdistan Journal of Applied Research, 2021)
Helicobacter pylori (H. pylori) bacteria are a microaerobic Gram negative that colonizes in the gastric and duodenum of human. It can cause prolong infection in the human life if not treated. Many of the studies showed that infection by H. pylori can cause some important gastrointestinal illness, such as peptic ulcer, chronic gastritis, gastric adenocarcinoma and mucosa associated lymphoid tissue lymphoma. Recurrence is generally considered as H. pylori recrudescence infection after one year of eradicated treatment. There are many factors involved in the H pylori reinfection, such as the epidemiology of H. pylori infection, condition of the live, development of economical state, and health conditions. The Objectives of this study were to estimate the incidence and determine the risk factors of infection by H. pylori bacteria in dyspeptic patients in Sulaimani city. And the Aims are to estimate prevalence of the Helicobacter pylori and patients’ characteristics in Sulaimani city. This is a cross-sectional study, using a Urea breath test or stained the gastric sample with Giemsa stain, which is including adult participants aged (12-87) years during the period starting from 1 January until 31 December 2020 on Iraqi male and female patients were visiting –Center for Gastroenterology and Hepatology in Sulaimani, city, Iraq. Three hundred and four patients were included, all of them underwent Urea breath test only but eighty-one of the participants underwent endoscopy and stained the gastric sample with Giemsa stain. Urea breath test for Helicobacter pylori was positive in54.9% which have significant correlation with risk factor findings. Results: the incidence rate of H. pylori infection in our study is 54.9%, and mean age of the study participants was (40.49 ±16.39) one hundred and ninety-one cases 62.8% were female and 113 cases 37.2%were male. Infection by H. pylori bacteria is rife in dyspeptic patients; and is more common in the age group of 31-40 years. One of noninvasive test to diagnosis H. pylori is Urea breath test. In conclusions the rate of helicobacter pylori infection in our study is 54.9% among the symptomatic patients, and the overall incidence of H. pylori UBT and Giemsa stain detection rate were 73.4 and 26.6% respectively.